Especially security systems electric and hybrid cars - Smirnov, O.; Poyda, S.; Смирнов, О. П.; Пойда, С. В.; Смирнов, А. П. (Харківський національний автомобільно-дорожній університет, 2014)
This article deals with especially security systems of electric cars and hybrid cars. In the design of vehicles with high-traction batteries should provide additional measures of active and passive safety. The ways and means of improving the safety of electric drive.
Особливості систем безпеки електромобілів та гібридних автомобілів
Особенности систем безопасности электромобилей и гибридных автомобилей
Keywords: electric car; hybrid car; security systems; active safety; passive safety; high voltage batteries; електромобіль; гібридний автомобіль; системи безпеки; активна безпека; пасивна безпека; високовольтні акумуляторні батареї; электромобиль; гибридный автомобиль; системы безопасности; активная безопасность; пассивная безопасность; высоковольтные аккумуляторные батареи; 629.3